'n Teologies-dogmatiese beoordeling van die Suid-Afrikaanse grondwetlike konsep van menswaardigheid - N. Vorster (Acta Theologica)
Human dignity is the key foundational value of the South African Constitution. As constitutional value it informs constitutional interpretation at a range of levels. It is therefore important that the concept should be given a concrete content that is juridically applicable. This article examines the ethical content that courts are giving to human dignity and compares it with a reformed biblical view of human dignity. It concludes that the courts are mainly relying on the classical-liberal notion of dignity as an inherent inalienable characteristic of man to define human dignity. The main problem with the classical-liberal concept is that it is an abstract notion which is not based on empirical evidence. This makes it difficult to concretise the concept. It also overemphasises individual rights at the expense of social responsibility, which complicates the balancing of individual and social rights and leads to moral degeneration. The Reformed Christian view defines human dignity as a relational concept and not an inherent possession. It closely links right and responsibility, as well as individual and social rights. Although the Christian concept of human dignity is not juridically applicable in all of its dimensions it can help to contextualise and broaden the concept of human dignity within a South African context.